Detecção de Dengue virus em Aedes albopictus Skuse e pequenos mamíferos de fragmento florestal urbano - Tatiana Mingote Ferreira de Azara (2013)
Dengue is an arbovirus that it caused by Dengue virus and transmitted by Aedes aegypti in Brazil and A. albopictus in Southeast Asia. Currently, the only available measure to break the virus transmission chain its fighting the vectors involved in the transmission since there is no vaccine or specific medication. Aedes albopictus in forest remnants inside urban areas may be a link in the arboviruses transmission to man, as it features eclectic behavior regarding host-seeking habit, and these places have greater proximity to humans. The fauna survey of mosquitoes and small mammals present in urban forest remnants is needed to understand the dynamics of environmental change, mainly anthropogenic character. With this set up risk factors in certain habitats, this may be related to the movement of viral agents among wild, domestic and vector. The aim of this study was to detect the presence of Dengue virus in A. albopictus and wild small mammals present in Cerrado and Atlantic Forest remnants in urban area of Minas Gerais State, Brazil. Were collected monthly (April/2011 to May/2012 ) of mosquitoes and small mammals in different areas of remaining forest in Sabará/MG. Aedes albopictus was tested by real-time PCR for detection of Dengue virus. The mammals had blood collected for serological tests (ELISA and soroneutralization) and for viral detection by conventional PCR. We collected 26 mosquitoes species and eight of small mammals. It was found that the mosquitoes species profile varied according to local and show that they prefer some kind of habitats. There were positivity for DENV-1, DENV-2 and DENV-4 in 19 pools of A. albopictus. Serological tests of mammals were positive for all serotypes in two species, rodent and marsupial. In Brazil, this is the first report of virology and serology positive for dengue-virus in small mammals. Although up to now we dont understand what is the role of these species in dengue epidemiology, it is speculated to occur on-site maintenance of the virus, making small mammals as a source of infection for mosquitoes and disease interepidemic transmission. Since small mammals can also be used as a blood source for A. albopictus females, the species can come to participate in enzootic cycles of various pathogens in these animals, including dengue. With the new framework reported the possible transmission and maintenance of dengue in areas of remnant urban forest, the scope of the disease changes and leads to questioning and a differentiated approach to disease control in front of a new framework epidemiological reported.